TRAINING ON HOW TO PROVIDE COMPLEMENTARY FOODS FOR BABIES IN GEMPOLPADING VILLAGE, PUCUK, LAMONGAN: PELATIHAN CARA PEMBUATAN MAKANAN PENDAMPING ASI (MP-ASI) DI DESA GEMPOLPADING, PUCUK, LAMONGAN - Rukanah; Yunita Dyah Fitriani; Yuyun Farihatin (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Babies aged 6 months to 24 months is a very important period for the growth and development of children. Therefore, health workers have an important role in helping families to achieve it from complementary foods. Good foods can make their growth optimal. Complementary foods start from mashed and soft. Objective: This activity aims to provide education to mothers about the nutritional status of toddlers, complementary feeding, and motor development. Method: This activity was counseling and training on how to provide complementary foods. Participants of this activity were mothers who have children aged > 6 months to 24 months. Results: It shows an increase in knowledge about the importance of correct and proper complementary foods for babies which improves baby's appetite, baby's motor development, and how to monitor baby's growth. Breastfeeding mothers are motivated to implement the correct and age-appropriate complementary feeding. Conclusion: The participants who took part in this training looked very enthusiastic. It was evidenced by the participants' listening comprehension and understanding.